Fractal characterization of the oxidation structure in ZrB2-SiC composite after thermal shocks. (September 2019) - Qi, F; Meng, S H; Wu, P; Guo, H; Zhao, D; Chen, T
Abstract: The effect of the oxidation structure on the residual strength of ZrB2 -SiC composite after repeated thermal shocks was investigated. The silica-rich glasses on the oxidation surface and pores in the oxidation layer were characterized using the fractal geometry method. Their fractal dimensions were calculated by Box-counting method. The increase of silica-rich glasses and the decrease of pores contributed to the increase of the residual strength of ZrB2 -SiC after thermal shocks.